The Red Cross and the Geneva Conventions – 60 Years On - Red Cross, NZ (Victoria University of Wellington Law Review, 2010)
2009 marked the 60th anniversary of the Geneva Conventions, but the issues in the Conventions remain as relevant today given today's humanitarian challenges. The basic notion of the Conventions focuses on the life and dignity of the individual. There is also ongoing relevance in contemporary conflicts in regulating international armed conflicts and the conditions of detention. The article then discusses the current challenges relating to the Conventions, including the protection of health workers and the conduct of hostilities. The authors conclude that international entities alone cannot ensure respect for the Conventions, calling for broad and ongoing vigilance and commitment of national governments, armed forces, and armed groups.